Investigation of Neutron Cross Section for Iron in the ENDF Library with Pulsed Sphere Measurements. (2nd September 2019) - Dhakal, Sushil; Brune, Carl R.; Massey, Thomas N.; Grimes, Steven M.; Voinov, Alexander V.; Akhtar, Shamim; Ramirez, Anthony P. D.; Richard, Andrea L.
Abstract: This work investigates the quality of the ENDF 56 Fe cross-section libraries for describing the transport of fast neutrons in iron. We have used the D(d, n) 3 He reaction with a pulsed 7-MeV deuteron beam energy as a neutron source and analyzed the neutrons transmitted through two natural iron spheres of thicknesses 3 and 8 cm. The experimental neutron time-of-flight transmitted spectra for various angles are compared with MCNP simulations. Our result indicates the possibility of an underestimation of the nonelastic cross section and an overestimation of the elastic cross section for 56 Fe in the ENDF/B-VII.1 library for the neutron energy range of 7.2 to 10.2 MeV. Our result agrees qualitatively with the Ramsauer model and optical model calculations. This discrepancy in the library cross section might lead to an underestimation/overestimation of material damage in nuclear reactor calculations. A newer evaluation, ENDF/B-VIII.0, was released subsequent to the completion of the majority of this project. The new evaluation has a decreased elastic cross section and an increased inelastic cross section for 56 Fe in our energy range of interest, which agrees qualitatively with our result.